2019
DOI: 10.1021/acsnano.9b04731
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area MXene Electrode Array for Flexible Electronics

Abstract: MXenes, an emerging class of two-dimensional (2D) transition metal carbides and nitrides, have potential for application as high-performance, low-cost electrodes in organic field-effect transistors (OFETs) because of their water dispersibility, high conductivity, and work-function tunability. In this study, we successfully fabricated a large-scale, uniform Ti3C2T x MXene electrode array on a flexible plastic substrate for application in high-performance OFETs. The work function of the Ti3C2T x MXene electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(135 citation statements)
references
References 62 publications
1
129
1
Order By: Relevance
“…[79] The high electrical conductivity of Ti 3 C 2 T x MXene is extremely useful for electrodes in field-effect transistors (FETs). [118][119][120][121] Zhang et al reported spin-coated transparent Ti 3 C 2 T x MXene films with different thicknesses (t) and corresponding transmittances (T) by controlling the spinning speed and concentration of the MXene solution (Figure 5a-d). [32] The transmittance of the films decreases with an increase in the MXene thickness (from 93% at 4 nm thickness to 29% at 88 nm) (Figure 5e).…”
Section: Transparent and Flexible Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] The high electrical conductivity of Ti 3 C 2 T x MXene is extremely useful for electrodes in field-effect transistors (FETs). [118][119][120][121] Zhang et al reported spin-coated transparent Ti 3 C 2 T x MXene films with different thicknesses (t) and corresponding transmittances (T) by controlling the spinning speed and concentration of the MXene solution (Figure 5a-d). [32] The transmittance of the films decreases with an increase in the MXene thickness (from 93% at 4 nm thickness to 29% at 88 nm) (Figure 5e).…”
Section: Transparent and Flexible Electrodesmentioning
confidence: 99%
“…f) Output characteristics and h) transfer characteristics of n-type PTCDI-C8 OFETs with NH 3 -doped MXene (NMX) electrodes. a-h) Reproduced with permission [121]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…MXenes are a class of 2D metal carbides, carbonitrides, or nitrides that have an elementary structure composed of 2–5 layers of early transition metals intercalated by carbon and/or nitrogen layers; they have been attracting increasing research attention because of their excellent physical and chemical properties such as metallic conductivity, [ 1 ] water dispersibility, [ 2 ] high optical transparency (>97% per nm), [ 3 ] tunable work function, [ 4,5 ] electromagnetic interference (EMI) shielding effect, [ 6 ] photothermal effect, [ 7 ] good mechanical properties, [ 8 ] and antibacterial activity. [ 9 ] Since the discovery of Ti 3 C 2 T x MXene by Gogotsi's group in 2011, this MXene and its derivatives have demonstrated outstanding performance in various applications, such as energy storage, electronics, EMI shielding, sensors, water purification, and desalination.…”
Section: Figurementioning
confidence: 99%
“…Except for graphene (Di et al, 2008), MXene also shows great potential. Cho and coworkers employed two-dimensional Ti 3 C 2 T x MXene as electrodes to realize a high-performance OFETs array with both p-type and n-type OSCs, and flexible complementary logic circuits, such as NOT, NAND, and NOR, were fabricated via integration of p-type and n-type OFETs (Figures 6A,B; Lyu et al, 2019). In this work, the MXene not only exhibited its capability of acting as a highly conductive flexible electrode, but also played a crucial role in improving OFETs performance by lowering the carrier injection barrier.…”
Section: Osc/2d Hybrid Fets With 2d Materials Optimizing the Electronmentioning
confidence: 99%
“…The strategies to optimize the electronic structure of the conductive channel of OFETs devices presented in the above work can be summarized in the following manner: (i) employing 2D material nanosheets to construct charge transport pathways with higher conducting efficiency in the bulk of OSC layers (Liscio et al, 2011;Lyuleeva et al, 2018); (ii) establishing ambipolar OSC/2D hybrid FETs with parallel layers of OSC and 2D materials respectively working as n-type or p-type conductive channels (He X. et al, 2017;Yan et al, 2018); (iii) reducing the contact barriers between OSC channels and electrodes with proper 2D materials as source/drain electrodes (Di et al, 2008;Lyu et al, 2019). In addition, interface charge transfer doping between OSC and 2D layers is also of great potential to optimize the channel electronic structure and improve the OFETs performances.…”
Section: Osc/2d Hybrid Fets With 2d Materials Optimizing the Electronmentioning
confidence: 99%